2010
DOI: 10.1056/nejmoa0910501
|View full text |Cite|
|
Sign up to set email alerts
|

Bone Marrow Transplantation for Recessive Dystrophic Epidermolysis Bullosa

Abstract: Background Recessive dystrophic epidermolysis bullosa is an incurable, often fatal mucocutaneous blistering disease caused by mutations in COL7A1, the gene encoding type VII collagen (C7). On the basis of preclinical data showing biochemical correction and prolonged survival in col7−/− mice, we hypothesized that allogeneic marrow contains stem cells capable of ameliorating the manifestations of recessive dystrophic epidermolysis bullosa in humans. Methods Between October 2007 and August 2009, we treated seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
310
2
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 329 publications
(327 citation statements)
references
References 34 publications
4
310
2
11
Order By: Relevance
“…RDEB has been the subject of intense research over the past 20 y, and because it is a monogenic disorder, a cure would rely upon on the normal production of type VII collagen. Therefore, several current research approaches aim to restore collagen VII, including cell therapy (11,12,(18)(19)(20), gene therapy (11,12,(18)(19)(20), and, more recently, bone marrow transplantation (21,22). However, long-term success in treating RDEB is limited by the low proliferative capacity of keratinocytes and by the low efficiency of targeting the keratinocyte stem cell pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDEB has been the subject of intense research over the past 20 y, and because it is a monogenic disorder, a cure would rely upon on the normal production of type VII collagen. Therefore, several current research approaches aim to restore collagen VII, including cell therapy (11,12,(18)(19)(20), gene therapy (11,12,(18)(19)(20), and, more recently, bone marrow transplantation (21,22). However, long-term success in treating RDEB is limited by the low proliferative capacity of keratinocytes and by the low efficiency of targeting the keratinocyte stem cell pool.…”
Section: Discussionmentioning
confidence: 99%
“…If we can establish iPSCs from such revertant patches of skin, then the gene correction step can be eliminated altogether, and a source of spontaneously corrected iPSCs can be generated and differentiated into skin. Building on the use of bone marrow transplantation in skin diseases such as RDEB (21,22), patientspecific iPSCs could be administered topically as well as systemically to ameliorate skin disease using an outside-in as well as an inside-out approach aimed at corrective therapy for RDEB.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to skin injury, both embryonic and postnatal transplantation of BM cells into mice lacking the skin protein, type VII collagen (Col 7) as well as postnatal studies in mice lacking type XVII collagen, basement membrane components that normally help secure adhesion between the epidermal and dermal skin layers, have demonstrated the capacity of BM to promote skin wound healing and to correct the intrinsic basement membrane defect (18)(19)(20). Most recently, a clinical trial of allogeneic whole BMT in humans lacking Col 7 (who have the inherited blistering skin disorder, recessive dystrophic epidermolysis bullosa, RDEB; OMIM226600) (21) has demonstrated that BM cells can repair fragile skin and restore Col 7 expression in skin basement membrane (22).…”
mentioning
confidence: 99%
“…Recently, several molecular therapies are being investigated for the treatment of patients with different subtypes of EB, including ex vivo gene therapy, 1 protein replacement 2 and cellular therapy. [3][4][5][6][7] Herlitz junctional epidermolysis bullosa (HJEB) is one of the most severe variants of EB characterized by extensive mucocutaneous blistering and erosions at birth leading to early lethality. 8,9 HJEB, an autosomal recessive disease, is caused by mutations in any of the genes encoding the subunit polypeptides laminin-a3, laminin-b3 or laminin-w2 of the heterotrimeric laminin-332 protein.…”
Section: Introductionmentioning
confidence: 99%